Prerequisites and Factors of ICT Sector Development in Eastern Partnership Countries - Olga Sovetnikova (Vestnik Vitebskogo gosudarstvennogo tehnologičeskogo universiteta (Online), 2019)
The article analyzes the ICT sector in the Eastern partnership countries and identifies the factors influencing the development of the Internet economy. The rating of the e-government of the Eastern partnership countries was assessed; the main trends in the development of the startup industry were considered; recommendations for the development of the ICT sector for the Eastern partnership countries were developed.